Primary biliary cirrhosis: clinical and laboratory criteria of diagnostics and up-to-date treatment - L. Yu. Il’chenko; V. I. Reshetn’yak (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. To generalize literature and authors own data on clinical and laboratory criteria of primary biliary cirrhosis (PBC) diagnostics and treatment.Original positions. PBC is organ-specific autoimmune liver disease affecting predominantly women that is characterized by chronic progressing destruction of intrahepatic bile ducts with portal inflammation, resulting in development of liver cirrhosis (LC). АМА-positive (classical) variant of PBC with pruritus, jaundice, biochemical syndrome of cholestasis and revealing of AMA in diagnostic titer (more 1:40) in blood serum is defined; АМА-negative variant of PBC with lower biochemical and immunologic activity, lower frequency of extrahepatic manifestations, that, however, does not influence the prognosis and terms of LC progression; overlap syndrome with autoimmune hepatitis (AIH) – PBC/AIH (9,4%); asymptomatic course of PBC which is characterized by absence of clinical symptoms for a long period and manifestation of disease at the stage of LC complications. Prescription of ursodeoxycholic acid (UDCA) results in significant decrease of intensity or its complete relief of pruritus, improvement or normalization of biochemical parameters and histological pattern of the liver, suppression of liver fibrosis and cirrhosis progression, and to decrease of portal hypertension. Combined treatment of UDCA and budesonide is proposed.Conclusion. UDCA is pathogenicly proved treatment of PBC.